The Cambridge companion to the age of Constantine - Lenski, Noel Emmanuel (Cambridge companions to the ancient world, 2006)
The Cambridge Companion to the Age of Constantine offers students a comprehensive one-volume survey of this pivotal emperor and his times. Richly illustrated and designed as a readable survey accessible to all audiences, it also achieves a level of scholarly sophistication and a freshness of interpretation that will be welcomed by the experts. The volume is divided into five sections that examine political history, religion, social and economic history, art, and foreign relations during the reign of Constantine, who steered the Roman Empire on a course parallel with his own personal development. Each chapter examines the intimate interplay between emperor and empire, and between a powerful personality and his world. Collectively, they show how both were mutually affected in ways that shaped the world of Late Antiquity and even affect our own world today.